Generasi Insan Maju Berbasis dalam Perspektif Tafsir Penyucian Jiwa Al-Mizan Thabataba’i - Achmad, Achmad; Layyinah, Rahmatika; Rahman, Fadhlu (Hanifiya: Jurnal Studi Agama-Agama, 2019)
The perspective of materialism initiated by some western scholars has obscured the concept of man. One of them is limiting that humans are merely material, the implication is that the progress of a generation is determined by the abundance of material aspects. In addition, by limiting humans to materiality, it also affirms human limitations, due to limited material. If humans are only limited matter, when the material is destroyed, human existence ends. The above view is increasingly making efforts to foster materialism, thus giving serious problems to almost all social order. Of course the above view is not in accordance with the principles in the Koran. However, in some circles of Islam there is a similarity with materialists regarding the benchmarks of the success of a human progress that is through achievements that are materialistic and put aside the spiritual elements, one of which is the discourse of territorial control in the name of Islam carried by radical Islamism, even willing to do acts of terror that worry the public. Fatally, this was legitimized through their interpretation of the Koran. These two understandings, both materialism and radical Islamism are not able to create an advanced generation, because they deny the spiritual or psychological element of man which is the most principle for humans, which distinguishes humans from other creatures. In addition to the two contexts of the problem, Islam in the archipelago is geneologically has a character that tends to be spiritual, so it is not appropriate to develop the concept of an advanced archipelago based on materialistic achievements as promoted by modernist materialism and radical Islamism. Purification of souls interpreted by Thabathaba'i in Al-Mizan provides an advanced concept of spiritual construction based on the Qur'an which is essential and in line with the spiritual characteristics of the archipelago. From it, an important aspect of humanity, which is spirituality, is to be accommodated, and used as a motor to create an advanced spiritual person, without ignoring materiality. This paper seeks to uncover Thabathabai's interpretation and is contextualized with the views of Islamic and Sufi philosophers regarding the mentality of the soul and its relationship to human behavior with descriptive analysis methods. Thus the spiritual beings of the archipelago are developed going forward that accommodate all aspects of humanity and are based on the Qur'an.